2001
DOI: 10.1523/jneurosci.21-13-04582.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection from Delayed Postischemic Administration of a Metalloporphyrin Catalytic Antioxidant

Abstract: Reactive oxygen species contribute to ischemic brain injury. This study examined whether the porphyrin catalytic antioxidant manganese (III) meso-tetrakis (N-ethylpyridinium-2-yl)porphyrin (MnTE-2-PyP 5ϩ ) reduces oxidative stress and improves outcome from experimental cerebral ischemia. Rats that were subjected to 90 min focal ischemia and 7 d recovery were given MnTE-2-PyP 5ϩ (or vehicle) intracerebroventricularly 60 min before ischemia, or 5 or 90 min or 6 or 12 hr after reperfusion. Biomarkers of brain oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 64 publications
4
122
0
1
Order By: Relevance
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 55%
“…In all previous studies the data obtained with E. coli parallel the trends obtained in in vivo animal model studies [1][2][3][4][5][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]37]. Here we compare the effect of Mn II Br 8 TM-3-PyP 4+ , its metal-free porphyrin HBr 8 TM-3-PyP 3+ , and the para analogue Mn II Br 8 TM-4-PyP 4+ on the aerobic growth of an SOD-deficient E. coli strain.…”
Section: Protection Of Aerobic Growth Of Sod-deficient E Colimentioning
confidence: 65%
“…Stroke. The very first study on central nervous system injuries was done with MnTE-2-PyP 5þ at Duke University in a rat stroke model (199). Rats were subjected to a 90-min focal ischemia (via middle cerebral artery occlusion, MCAO).…”
Section: Central Nervous System Injuriesmentioning
confidence: 99%
“…The compound has further proven effective in protection of SOD-deficient E. coli (26) and in stroke (28,29), spinal cord injury (30,31), diabetes (32,33), sickle cell disease (34), and radiation/cancer (35-38) rodent models of oxidative stress injuries. Much like SOD (1, 9, 21, 22) its high catalytic potency has been ascribed both to the favorable redox properties of the metal center and to the effect of the positively charged ortho-N-ethylpyridyl nitrogens that provide electrostatic facilitation for the approach of the negatively charged superoxide (23).…”
mentioning
confidence: 99%